2022
DOI: 10.1016/j.jaim.2020.08.004
|View full text |Cite
|
Sign up to set email alerts
|

An Ayurvedic personalized prophylactic protocol in COVID-19

Abstract: The current COVID-19 pandemic brought about by the SARS-CoV-2, a novel β coronavirus is creating intense health havoc globally. Researchers suspect the situation to stay for long in the community, considering this virus’s pathogenesis, high rate transmission and tendency to provoke uncontrolled immune response activation. Immune mechanisms are highly individualistic. We put forward a hypothetical model of p rakruti (Ayurvedic body phenotyping character) based personalized pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Ayurveda experts have suggested that COVID-19 presents with features comparable to Vatakaphajvara, which can become Sannipatajvara [26][27] [28] with severe presentation, complications and even death in some patients. VK is indicated for the management of Vatakaphajvara and hence has been recommended for management of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Ayurveda experts have suggested that COVID-19 presents with features comparable to Vatakaphajvara, which can become Sannipatajvara [26][27] [28] with severe presentation, complications and even death in some patients. VK is indicated for the management of Vatakaphajvara and hence has been recommended for management of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the anti-inflammatory cholinergic pathway, which is a function of the efferent vagus nerve, is crucial in regulating systemic and local inflammation, making neuronal immunomodulation possible. [23] Herbs contain immune-stimulating and inflammation-modulating characteristics, which can help prevent life-threatening illnesses when used to treat viral respiratory disease. The holistic approach of Ayurveda emphasises illness prevention through lifestyle modifications, dietary management, immune-boosting measures, and symptom treatment with herbal medicines.…”
Section: Role Of Ayurveda In Immunomodulation and Antiviral Activitymentioning
confidence: 99%
“…As a result, customised therapy is critical for establishing improved host homeostasis in all immune system diseases that affect people, whether infectious or not. [23] Agantu (exogenous) Jwara is the primary aetiology, and it causes Rasavaha Srotas symptoms including tastelessness, headaches, vomiting, and body pains. The indications of Pranavaha and Raktavaha Srotas follow.…”
Section: Ayurveda and Inflammationmentioning
confidence: 99%
“…Traditional medicinal practices based on herbs and their extracts are gaining momentum. Their formulations are widely given with supplementary allopathic treatment for the earlier recovery ( Ang et al, 2020 ; Mhya et al, 2021 ; Vanshylla et al, 2021 ; Ashande et al, 2022 ; Nair et al, 2022 ). Syzygiumaromaticum, a native species of the Maluku Islands in Indonesia, traditionally found its importance as a flavoring additive for food.…”
Section: Introductionmentioning
confidence: 99%